Estuarine production of resident and nursery fish species: Conditioning by drought events? - Dolbeth, M. (2008)
The production of resident (Pomatoschistus minutus and Pomatoschistus microps) and marine juvenile fish species using the Mondego estuary (central Portugal) as nursery grounds (Dicentrarchus labrax, Platichthys flesus, Solea solea), was assessed in order to: (1) understand the potential of the estuary for fish production; (2) know the production of nursery fish species likely to be exported to the coastal stocks; and (3) how anthropogenic and natural stress could influence the estimated production. Sampling occurred from June 2003 to May 2006 and together the 5 species in study comprised around 70% of the whole fish community numbers and biomass. Increasing drought conditions were observed, starting with a normal hydrological year in 2003 until attaining a severe drought in 2005, which resulted in low river discharges (1/3 of the mean river discharges in 2003). Additionally, high water temperatures were observed in 2003 and 2005 (24 and 26 °C, night temperatures). The secondary production was estimated using the increment summation method, after recognition of the cohorts. Production was in general lower in the Mondego estuary when compared to other systems, which was associated to the estuary's small area (only 3.4 km2, less than 1/4 of area compared to other studied systems). Dicentrarchus labrax was among the most productive species. Production decreased in the drought year for all species, especially evident for D. labrax, P. minutus and P. flesus. No direct effects could be attributable to the salinity and temperature variations and to the low freshwater discharges (resulting from the drought and high temperatures), yet these were pointed as probable major reasons for the decreased production. A significant reduction (15-45% reduction in the estuarine production) was also concluded for the potential production to be exported for coastal areas by the nursery species in the drought conditions.